Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 5 - Number Theory and the Real Number System - Chapter Summary, Review, and Test - Review Exercises - Page 335: 75



Work Step by Step

Simplify each radical to obtain: $=2\sqrt{9(2)} + 3\sqrt{4(2)} \\=2\sqrt{3^2(2)}+3\sqrt{2^2(2)} \\=2(3)\sqrt2 +3(2)\sqrt2 \\=6\sqrt2+6\sqrt2 \\=\sqrt2(6+6) \\=\sqrt2(12) \\=12\sqrt2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.